2018
DOI: 10.1002/adma.201706504
|View full text |Cite
|
Sign up to set email alerts
|

Orientation‐Dependent Strain Relaxation and Chemical Functionalization of Graphene on a Cu(111) Foil

Abstract: Epitaxial graphene grown on single crystal Cu(111) foils by chemical vapor deposition is found to be free of wrinkles and under biaxial compressive strain. The compressive strain in the epitaxial regions (0.25-0.40%) is higher than regions where the graphene is not epitaxial with the underlying surface (0.20-0.25%). This orientation-dependent strain relaxation is through the loss of local adhesion and the generation of graphene wrinkles. Density functional theory calculations suggest a large frictional force b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…[13] An AFM image revealed wrinkled FGR covered with Ni 2 PN Ss,w ith an overall thickness of about 3.2 nm (Figure 2c). [14] Considering that the average thickness of as ingle Ni 2 Pl ayer is approximately 2.4 nm ( Figure S4), the apparent thickness of graphene is about 0.8 nm, which is consistent with the thickness of monolayer FGR. Theu ltrathin 2D Ni 2 Ps tructure was further confirmed by TEM analysis (Figure 2d).…”
supporting
confidence: 73%
“…[13] An AFM image revealed wrinkled FGR covered with Ni 2 PN Ss,w ith an overall thickness of about 3.2 nm (Figure 2c). [14] Considering that the average thickness of as ingle Ni 2 Pl ayer is approximately 2.4 nm ( Figure S4), the apparent thickness of graphene is about 0.8 nm, which is consistent with the thickness of monolayer FGR. Theu ltrathin 2D Ni 2 Ps tructure was further confirmed by TEM analysis (Figure 2d).…”
supporting
confidence: 73%
“…Considering the distinct atomic configurations of Cu crystal surfaces, both strain level and direction are different for graphene grown on them. Recently, a few groups have reported that graphene grown on Cu(111) can be free of wrinkle due to the strong interfacial coupling or large friction force between graphene and Cu(111). However, the detailed corrugation process of graphene on various Cu crystal surfaces, including the existence and extent of step bunches, the distribution of graphene wrinkles, and their relationship for the strain relaxation, are not fully revealed.…”
mentioning
confidence: 99%
“…And the authors attributed this heterogeneous oxidation strength of graphene-Cu system to the degree of latticealignment, which results in a varying average height of carbon atoms above the global Cu surface. As well as, Li et al's experiments and calculations [108] also proved that CVD graphene epitaxially grown on the single crystal Cu(111) surface has much friction with the substrate, forming an obvious energy barrier and inhibiting the formation of wrinkles in graphene, thus inhibiting the corrosion of Cu.…”
Section: Lattice-misalignment-originated Oxidation Of Copper Under Grmentioning
confidence: 87%